Volumetric analysis of tumor control following subtotal and near‐total resection of vestibular schwannoma. (24th November 2015) - Jacob, Jeffrey T.; Carlson, Matthew L.; Driscoll, Colin L.; Link, Michael J.
Abstract : Objectives/Hypothesis: The primary goals of microsurgery for vestibular schwannoma (VS) include preservation of neural function and complete tumor removal. In a subset of patients, adherent tumor remnant may be intentionally left behind in order to minimize risk of new neurologic deficits. It is not well established if residual tumor volume predicts likelihood of tumor remnant growth. Methods: Patients with sporadic VS who underwent near‐total (NTR) or subtotal (STR) VS resection between 2000 and 2014 were reviewed. Postoperative tumor remnants were volumetrically contoured using T1‐weighted gadolinium‐enhanced magnetic resonance imaging obtained within 3 months of surgery. Results: A total of 103 patients met study criteria, and the median duration of radiographic follow‐up was 41 months (mean 56.1 months, range 12–150 months). Fifty patients underwent NTR and 53 received STR. Overall 14 (13.6%) tumors recurred at a median of 41.0 months. Patients who underwent STR were over 13 times more likely to recur compared with those treated with NTR (hazard ratio 13.31; 95% confidence interval 1.71–103.91; P = 0.014). The median time to recurrence following NTR was 124 months compared to 32 months after STR ( P < 0.001). Conclusions: Long‐term follow‐up in patients undergoing incomplete resection is essential. Near‐total resection has a significantly lower rate of recurrence compared to STR. Maximal surgical resection should be the goal in VS microsurgery. The decision to pursue less than complete resection should be based on intraoperative impression, when it is felt that continued dissection of adherent disease would compromise neurologic outcome. Level of Evidence: 4. Laryngoscope, 126:1877–1882, 2016